Need for restrictive criteria to define symptomatic cholelithiasis to avoid unnecessary cholecystectomies-evidence from the literature review - Nabi, Naveed (International Surgery Journal, 2021)
Gall stone disease (GSD) is one among the most common reasons for which patients flock the office of general surgeons and cholecystectomy is one of the most common surgeries performed worldwide. Though majority of the patients are asymptomatic but a considerable number among them are deprived of their vital gall bladder for just or unjust reasons. With the introduction of laparoscopic cholecystectomy, there has been significant escalation in unnecessary cholecystectomies leading to excessive burden on health care system as well as subjecting patients to undue surgical risk. Considering the benign natural history of GSD, a restrictive strategy should be adopted while deciding surgical management for GSD. In this article, the author has given evidence from already published literature to support his views. Preoperative and sincere assessment of each symptom with exclusion of functional disorders and due consideration of patient’s life expectancy are paramount in reducing unnecessary cholecystectomies as well as ensuring long tern relief of symptoms post-surgery.